2005
DOI: 10.1080/10511482.2005.9521531
|View full text |Cite
|
Sign up to set email alerts
|

Public housing transformation and the hard‐to‐house

Abstract: The transformation of public housing will necessarily have profound effects on the lives of thousands of very vulnerable families. For three decades, public housing served as the housing of last resort, with federal regulations increasingly favoring the neediest households. But this transformation has meant dramatic changes in federal policy for housing the poor by promoting mixed-income housing and the use of vouchers to prevent the concentration of troubled, low-income households. This transformation has lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 7 publications
(9 reference statements)
1
43
0
1
Order By: Relevance
“…I am summarizing the most prominent of these trends disturbing trends under "Findings." These finding are consistent with the results of other HOPE VI site studies in the USA (Feldman 2007;McInnis et al 2007;Popkin et al 2004a, b;Popkin et al 2005;Smith and Housing 2002).…”
supporting
confidence: 91%
“…I am summarizing the most prominent of these trends disturbing trends under "Findings." These finding are consistent with the results of other HOPE VI site studies in the USA (Feldman 2007;McInnis et al 2007;Popkin et al 2004a, b;Popkin et al 2005;Smith and Housing 2002).…”
supporting
confidence: 91%
“…31 This recommendation is consistent with a wide range of research showing how concentrations of disadvantaged households adversely affect neighborhoods (Galster, Cutsinger, and Malega, 2008;Galster et al, 2003). How to best prevent such reconcentration has been discussed at considerable length (Briggs, Popkin, and Goering, 2010;Galster et al, 2003;Grigsby and Bourassa, 2004;Turner, 2008, 2001;Pendall, 2000;Popkin and Cunningham, 1999;Popkin, Cunningham, and Burt, 2005;Turner and Williams, 1998).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…or assisted housing has been demolished and ''vouchered out'' in favor of mixedincome redevelopment (Popkin, Cunningham, and Burt 2005;Popkin and Cove 2007;Snell and Duncan 2006;Walker 2000, 2007) and in recent desegregation programs (Pashup et al 2005); and (b) limited time, money, transportation, information, and other resources important to effective housing search (Basolo and Nguyen 2006;Pashup et al 2005). Where information for search is concerned, Varady and Walker's (2007) multi-city study of vouchering out found that voucher holders leaving public housing were more likely to find out about available apartments from friends and relatives, newspaper ads, or real estate listings than from housing counselors.…”
mentioning
confidence: 99%